Multi-level factors influencing climate migration willingness among small-scale farmers - Kalantari, Razieh; Pakravan-Charvadeh, Mohammad Reza; Rahimian, Mehdi (Frontiers in Environmental Science, 2024)
Climate change is a pressing global challenge impacting agriculture and rural communities. This study investigates the willingness to migrate against climate change among small-scale farmers and explores the associated socioeconomic and sociodemographic factors. A sample of 296 small-scale farmers was randomly selected, and data were collected through face-to-face interviews. The results showed that different dimensions of adaptation strategies are inversely associated with willingness to migrate in response to climate change. In contrast, human capital was directly associated with the desire to migrate. Also, improving financial capital was indirectly associated with farmers' willingness to migrate to the rural area. The study also found that education level plays a key role in increasing the probability of being willing to relocate in response to climate change. Specifically, a one-year increase in education level was associated with a 4.2% increase in the likelihood of being willing to migrate. Therefore, providing financial support for sustainable farming practices to alleviate the economic challenges faced by smallscale farmers, and implementing targeted capacity-building programs to enhance farmers' adaptive capacity and promote sustainable agricultural development can be suggested. Furthermore, improving farmers' specialized knowledge regarding the various consequences of climate migration, in conjunction with their general education, can help control and manage their migration.